(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
The article explores the history, meaning, and importance of inclusive education; outlines its methodological underpinnings, aims, and objectives; and supports the humanistic nature of the pedagogical principles and conceptual ideas of inclusive education as well as their potential for application.